Trends for Diarrhea Morbidity in the Jasikan District of Ghana: Estimates from District Level Diarrhea Surveillance Data, 2012–2016 - John Tetteh; Wisdom Kwami Takramah; Martin Amogre Ayanore; Augustine Adoliba Ayanore; Elijah Bisung; Josiah Alamu (Journal of Tropical Medicine)
About 22% of childhood deaths in developing countries are attributable to diarrhea. In poor resource settings, diarrhea morbidities are correlated with poverty and socio-contextual factors. Diarrhea rates in Ghana are reported to be high, with cases estimated at 113,786 among children under-five years in 2011. This study analyzed the trends of diarrhea morbidity outcomes in the Jasikan District of Ghana. A retrospective analysis of records on diarrhea data for a five years’ period (January 2012 to December 2016) was undertaken. There was a total of 17740 diarrhea case reports extracted from District Health Information Management System (DHIMS) II database in an Excel format which was then exported to Stata version 14 for data cleaning, verification, and analysis. Excel version 2016 was used to plot the actual observed cases by years to assess trends and seasonality. There was a period incidence rate of 272.02 per 1000 persons with a decreasing annual growth rate of 1.85%. Declines for diarrhea generally occurred from November to December and increased from January upwards, evidence that most cases of diarrhea in this study were reported in the harmattan season. High incidence of diarrhea was found to be common among under-five children and among females. Decreasing trend of diarrhea incidence which was identified in this research within the five years’ period understudied shows that, by the year 2020, there will be a sharp decline in the incidence rate of diarrhea reported cases in Jasikan District, given improvements in the external environmental conditions in the district, all things being equal.